بنک المعرفى المصرى ودوره فى دعم وتطویر التعلیم الثانوى العام : دراسة میدانیة لاستطلاع آراء المعلمین - د. اسماء حسین محمد Hussein (المجلة الدولية لعلوم المكتبات والمعلومات)
from Egypt's 2030 vision for sustainable Development, and the strategicplan for the development of pre-university education and the associatedoperational programs, it is clear that the development of the secondary educationsystem is important, and that the students ' ability to think and innovate isincreased, and with the state's interest in implementing many Infrastructure,construction, roads and new cities projects the Egyptian Knowledge Bank,launched in January 2016, remains one of the most important, sustainable andinfluential projects of the country, and the project's priorities are investment inpeople, not stoneAs is known, the Egyptian Knowledge Bank (EKB) is one of the mainpillars of the initiative of President Abdel Fattah al-Sisi "Towards an Egyptiansociety that learns, thinks and Innovates" which was launched on Flag Day 2015,with the aim of spreading science and knowledge, supporting education andscientific research, and improving its output and interest in classifying Egyptianuniversities and support the research capabilities of young researchers and theestablishment of a unified system for the publication of journals and scientificconferences as well as university theses.All agree that secondary education needs the concrete efforts of all theDecision makers, experienced and competent, for reform and development ,hence the importance of this study to know the importance of the Egyptianknowledge Bank and its role in supporting and developing general secondaryeducation in Alexandria. through the survey of teachers at the secondary schoolsin Alexandria Governorate about the Egyptian knowledge Bank and itsusefulness in supporting education and curriculum, and the extent to whichteachers encourage students to use the Egyptian knowledge Bank in teachingand learning processes, as well as The skills needed for teachers to deal with theEgyptian knowledge Bank and benefit from it in education